Changes in Physical Function, Cognitive Function, Mental Health, and Sleep Quality After Cardiac Surgeries and Procedures - Yoshimi Kawahara; Nobuto Nakanishi; Keiko Nomura; Satoshi Doi; Jun Oto (Nursing Reports, 2025)
Background: Patients who undergo cardiac surgery and procedures often experience functional impairments. However, few studies have compared changes in physical function, cognitive function, mental health, and sleep quality before and after the interventions. Methods: Intensive care unit (ICU) nurses visited the ward and conducted the assessments. The Japanese version of the Cardiovascular Health Study (J-CHS) and the Barthel index for physical function, mini-mental state examination (MMSE) for cognitive function, hospital anxiety and depression scale for anxiety (HADS-A) and depression (HADS-D) for mental health, and a 5-point Likert scale for sleep quality were used. Results: Of the 210 cases, 156 were included. Cardiac surgeries and procedures included valve replacement or valvuloplasty (43%), coronary artery bypass graft (9%), and transcatheter aortic valve implantation (39%). At a median of 7 (4–9) days after ICU discharge, the J-CHS score worsened from 2 (1–3) to 3 (2–3) (p < 0.01), and the Barthel index worsened from 95 (85–100) to 75 (55–85) (p < 0.01). The HADS-A score improved from 3 (1–6) to 1 (0–4) (p < 0.01), and the HADS-D score improved from 4 (1–7) to 2 (1–6) (p < 0.01). The MMSE score remained unchanged at 26 (24–29; p = 0.91). Sleep quality worsened from 4 (3–5) to 3 (2–4) (p < 0.01). In the multivariate analysis, sleep quality deterioration was associated with open thoracotomy. Conclusions: After cardiac surgeries and procedures, physical function and sleep quality worsened, whereas anxiety and depression improved, and cognitive function remained unchanged.